(Re)Printing and Copyright in the Beginning of the 20th Century in Bosnia and Herzegovina - Hana Younis (Bosniaca, 2020)
This work focuses on the Walny vs. Kajon copyright infringement case, showing the situation in Bosnia and Herzegovina within this field during the Austro-Hungarian rule. The author shows how copyright was legally regulated and how it could have led to infringement, through methods of (re)printing of Plan von Sarajevo und Umgebung. Participants of this legal case are well known to public, as writers, owners and editors of respectable journals and printing houses. For this reason, this case deserves some special attention.